IN VITRO ANTIBACTERIAL, ANTIOXIDANT AND HEPATOPROTECTIVE EFFECT OF CURCUMIN-ZINC OXIDE NANO-PARTICLES IN COMBINATION - AMAL SABRY OTHMAN,; MOHAMMED ABDALLA HUSSEIN, (International Journal of Pharma and Bio Sciences, 2015)
Nanoparticles have selective toxicity to bacteria but exhibit minimal effects on human cells. This study was carried out to investigate the antibacterial activity and potential hepatoprotective effect of curcumin-zinc oxide nanoparticles (1:1, w/w) on paracetamol-induced injury in rat hepatocytes. It was found that concentration 30μg was the highly effective against gram negative strains while concentration 10 μg was the most effective against gram positive strains. These strains were first examined by some antibiotic groups to detect the MDR ones. It was found that only Streptococcus faecalis was MDR. Escherichia coli and Salmonella typhi were the mostly affected strains they were scanned by TEM and it was found that nano curcumin affected the bacterial cell membrane and internal cell content. DNA fragmentation was done for Salmonella typhi and it revealed no change in DNA fragmentation. Also, incubation of hepatocytes with paracetamol resulted in increased formation of thiobarbaturic acid reactive substances (TBARS) with a parallel increase in lactate dehydrogenase (LDH) leakage as 1h following incubation. Time-dependent depletion of cellular reduces glutathione (GSH) was observed starting 2h following incubation with paracetamol. Incubation of hepatocytes with curcumin-ZnO nano-particles markedly protected against paracetamol-induced formation of TBARS, increase in LDH leakage and prevented GSH depletion. 20 μg is the most effective doses for curcumin-ZnO nano-particles. The results clearly suggest that curcumin-ZnO nano-particles in combination exerted a hepatoprotective effect against hepatotoxicity induced by paracetmol more pronounced than vitamin C.